KEDUDUKAN HARTA BAWAAN (HARTA ASAL) DALAM PROSES PERALIHAN HAK MENURUT PRESPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Lily Andayani; Sherly M. Imam Slamet; Indah Dwiprigitaningtias (Universitas Jenderal Ahmad Yani, 2024)
Marriage is a legal relationship that is a legal relationship between a man and a woman who have fulfilled the requirements of marriage according to the provisions, for as long as possible. The position of property in the marriage is different, so that it will result in different rights to the property. Not all marriages run smoothly, so that it can result in the termination of marital relations either due to the death of one of the parties (divorce dead) or divorce (divorce alive). One of the legal consequences of a marital bond is the formation of marital property. The classification of marital property is included in the problem, resulting in difficulties or harm to third parties in the event of a transfer of rights.